Involving Youth in Local Governance - Nayakara Veeresha (KILA Journal of Local Governance, 2013)
Governance of India underwent progressive changes since the 73 rd and 74 th Constitutional Amendment Acts in the year 1992. The introduction of reservation for Women, SC, and ST and reduction in the voting age from 21 to 18 resulted in making governance inclusive in nature. Various state governments such as West Bengal, Karnataka, Kerala, Madhya Pradesh, etc. initiated well intended measures to enhance people’s participation in the planning and development process. Steps such as People’s Plan Campaign in Kerala) and Palli Sabha in Madhya Pradesh are laudable. With emerging complexities in national life, the country needs young minds that can generate new ideas of good governance. This paper brings to light the need to involve the youth in the decision-making process, especially in the context of local governance.